(untitled) (Medico Legal Update, 2020)
Albert Einstein once said in relation to justice that, “in matters of truth and justice, there is no difference between large and small problems, for issues concerning the treatment of people are all the same”. The Preamble of the constitution of India states that,“We, the People of India having solemnly resolved to constitute India into a Sovereign, Socialist, Secular, Democratic, Republic and to secure to all its citizens; Justice, social, economic, political;Liberty of thought, expression, belief, faith and worship;Equality of status and opportunity; and to promote among them all;Fraternity, assuring the dignity of the individual and the unity and integrity of the nation.” But still after so many years of Independence we have several rules, regulations and mechanisms but those are not adequate to give justice. The establishing father of our constitution placed Justice at the highest level and India is considered to be the largest democracy still we are not getting fair justice. It is a still remain a demand and need to be resolved soon.